DESIGN AND STUDY A NEW TELESCOPIC ARM USED IN NARROW SPACE - LIU XiangYong; LI WanLi; WANG WenJia (Jixie qiangdu)
As it is difficult to check water pumps and fuel boiler pipes,design and study a telescopic boom used in narrow space.Adopt steel tape to design telescopic arm,and the tapes’ edges are welded to form mechanical arm.Motor drive the divided wheel by gears,divided wheel drive steel tape to stretch,and telescopic boom has curly storage function.The arm’s section parameters include thickness,central angle,arc length;By the thin shell theory,analyze and calculate the central angle.Based on the Workbench software,analyze the central angle and thickness’ s infiuences to X and Y direction deformation.Results show that with the increase of central angle,the Y direction deformation decreases gradually,and the X direction deformation increases gradually.Deformation rate changes quickly before 40 °,and changes slowly after 40 °.With the increasement of thickness,the X and Y direction’s deformation rate are smaller.Based on theory and simulation,the final thickness is 0.1 mm and the central angle is 45 °.Finaly through experiments,verify the arm’s section parameters and bearing capacity.